Biocompatible Nanoparticles: High‐Resolution Label‐Free Detection of Biocompatible Polymeric Nanoparticles in Cells (Part. Part. Syst. Charact. 3/2018). (25th March 2018) - Pancani, Elisabetta; Mathurin, Jérémie; Bilent, Sylvie; Bernet‐Camard, Marie‐Françoise; Dazzi, Alexandre; Deniset‐Besseau, Ariane; Gref, Ruxandra
Abstract : Biodegradable polymeric nanoparticles are among the most employed nanocarriers for drug delivery and the design of efficient drug nanocarriers requires a mechanistic insight into their interaction with targeted cells. In article number1700457, Ariane Deniset‐Besseau, Ruxandra Gref and co‐workers develop an infrared nanospectroscopy (nanoIR) as a high‐resolution method for the precise detection and simultaneous identification of nanoparticles chemical composition in cells.